Study and investigation of Solar water heating system using Phase change material (PCM)-Review (International Journal of Advanced Research in Science, Management and Technology, 2015)
In order to utilize the solar energy from the sun at all times energy should be stored and used when needed. Phase change material is a viable for storing thermal energy in solar water heating system and has the advantages of its isothermal behaviour during the charging and discharging processes and high energy storage density. They store 5 to 15 times more amount of heat per unit volume than sensible storage materials. The application of PCM in heating and cooling systems is to improve overall efficiency of system and reduce electrical power consumption and greenhouse gas emission.Review paper summarizes works on solar water heating system with thermal energy storage material and compatibility between HTF, heat exchanger and/ or storage material. Heat storage in phase change materials is an advantage of compactness of system and heat supply at constant temperature in heating and cooling applications. Thermal energy loss by the system can be reduce by different type of systems integrate with PCM into solar collector, hot water tank, duct, heat exchanger technology and due to system efficiency increases. This study helps to develop new advance experimental setup of solar water heating system with PCM.
Keywords: Solar water heating system, Latent heat storage materials, Hot water tank, Solar collector.